Banana diversity in the Middle East (Jordan, Egypt, Oman) - Langhe, E. de; International Network for the Improvement of Banana and Plantain (2002)
The International Network for the Improvement of Banana and Plantain (INIBAP) organized a survey of banana diversity in the Middle East in collaboration with the Food and Agriculture Organization (FAO). It was the first effort at the international level to systematically explore banana cultivar diversity in the Middle East region. A consistent literature on the subject does not seem to exist. Indeed the few indications of diversity, found in incidental reports, papers, or references to the latter, are either not dealing with taxonomic aspects, or have not been confirmed afterwards. The survey clarified the situation at least for the three countries visited. The diversity in traditional bananas is a small to moderate one, depending on the country. With the practical consequence that the introduction of other cultivars or of new hybrids is a matter that deserves serious attention, especially in order to meet the perceived difficulties experienced by small-to-moderate income farmers. This reality brought the survey team to spend some time on the agronomical and economical aspects of banana cultivation in each country. This effort is reflected in the recommendations formulated for each visited country, based as they are on the observations and discussions that could be carried out within the rather limited time dedicated to the survey. The majority of the findings and respective recommendations however, deal with the taxonomical clarification of the observed banana cultivar diversity in the visited countries, thus conforming to the main objective of the survey.